PENGARUH PERSEPSI KEYAKINAN DAN BAGI HASIL TERHADAP MINAT MENABUNG DI BANK SYARIAH - Sugeng Hariadi; Sari Angriani (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2018)
Islamic Banking is a banking institution that runs with the principles of sharia. In every business activity, Islamic banks always use the laws of Islam listed in the Qur’an and Hadith. This study aims to determine the influence of perceptions of beliefs, and profit sharing perceptions of interest in saving. This research is a quantitative descriptive research with survey method. The population in this study are Surabaya students who are saving in Bank Sharia. Instrument test, classical assumption test, and data analysis test in this study using SPSS. From the results of the study, it is known that the perception of belief has a positive and significant effect to the interest of saving, and the perception of the results have a positive and significant impact on interest in saving.